MENANAMKAN NILAI-NILAI KARAKTER BERBASIS KEARIFAN LOKAL DI SDN 7 BATUDAA - Badaru, Indira Oktaviyani; Pomalingo, Samsi; Sarlin, Muhammad (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to (1) Determine the form of local wisdom in SDN 7 Batudaa, 2) Determine the strategy of instilling character based on local wisdom in SDN 7 Batudaa. 3) Determine the implementation of instilling character based on local wisdom in SDN 7 Batudaa. The method used in this study is a qualitative method. The data sources in this study are: (1) Principal, Vice Principal for Curriculum (3) Civics Teacher (4) Students. Data collection techniques use observation, documentation and questionnaires. Data analysis used is thematic analysis. The results of the study show (1) The form of local wisdom developed in SDN 7 Batudaa is diverse, including regional arts such as traditional dances such as the tidi lo maluo dance, local regional languages, community mutual cooperation to the love of local culinary. 2) The strategy in instilling character based on local wisdom in SDN 7 Batudaa is by providing supporting facilities, inviting tutors from outside to train students to be able to dance regional dances. Then cooperate with parents and the local community. 3) Implementation of local wisdom in instilling character values ​​in students at SDN 7 Batudaa, namely discipline, mutual respect and protecting nature so that it is not damaged because local wisdom is knowing and loving cultural heritage, both natural cultural heritage, human resource heritage and as a marker of communication identity.